Survey of anti-obesity drug prescribing for obese children and young people in UK primary care. - White,B; Hsia,Y; Kinra,S; Saxena,S; Christie,D; Viner,RM; Wong,ICK (BMJ Paediatrics Open, 2017)
Objectives Antiobesity drug (AOD) prescribing in childrenand young people (CYP) in primary care is rising with highrates of discontinuation. Little is known about prescribingin this group in terms of patient demographics andcomorbidities, reasons for initiation and discontinuation, oradherence to national guidelines.Design Questionnaire survey to general practitioners(GPs) identified using a nationally representative primarycare database covering 6% of UK population.Setting UK-wide primary care.Participants Patients were eligible if prescribed anAOD aged ≤18 years between 2010 and 2012. A total of151 patients from 108 unique practices were identifiedvia national prescribing database, with responses for 119patients (79%) from 84 practices; 94 of 119 (79%) wereeligible for inclusion.Primary and secondary outcomes Survey of GPprescribing habits of AODs to CYP. We audited orlistatusage against the National Institute for Health and CareExcellence (NICE) guidance.Results 47% were prescribed metformin, 59% orlistatand 5% both drugs. Orlistat was largely prescribed by GPsindependently (49/55 prescriptions, 89%) and metforminby GPs on specialist recommendation (12/44, 27%).Orlistat was largely prescribed in those over 16 yearsof age without physical comorbidities. Metformin wasinitiated for treatment of polycystic ovarian syndrome(70%), insulin resistance (25%) and impaired glucosecontrol (9%). Median supply of metformin was 10.5months (IQR 4–18.5 months) and 2.0 months (1.0–4.0) fororlistat (p≤0.001). Drug terminations were largely due tofamilies not requesting repeat prescriptions. NICE guidanceadherence was low; 17% of orlistat prescriptions wereinitiated by specialists, and 56% had evidence of obesityrelatedcomorbidity. GPs reported lower confidence inprescribing AOD to CYP compared with adults (10-pointLikert score median 3 vs 8, p<0.001).Conclusions Prescribing of AOD in primary care ischallenging with low adherence to NICE guidance. Furtherwork is